A Method to Measure Myeloarchitecture of the Murine Cerebral Cortex in vivo and ex vivo by Intrinsic Third-Harmonic Generation - Redlich, Michael J.; Lim, Hyungsik (Frontiers in Neuroanatomy, 2019)
A new label-free method is presented for measuring myeloarchitecture of the murine cerebral cortex in vivo and ex vivo. Growing evidence suggests that cortical myelination plays significant roles in neuronal plasticity and pathologies, such as multiple sclerosis (MS), but illuminating the mechanism requires longitudinal imaging of the same brains. Here we demonstrate imaging unlabeled myelinated fibers in a live mouse brain by third-harmonic generation (THG). Contrary to other label-free microscopies based on reflectance, fibers of all orientations could be visualized, i.e., radial and tangential to the pia, which is suitable for revealing the three-dimensional connectivity. The depth of THG imaging in an intact brain was approximately 200 μm, so the network of myelinated fibers could be captured into layers 2/3 in vivo. THG provides a novel base for reconstruction of morphology. Semi-automatic tracing of THG-positive axons unraveled the depth-dependent distribution of the myelin lattice. Finally, a unique light property of THG was exploited for the estimation of the g-ratio. The demonstrated THG morphometry of the length density, orientation, and sheath thickness of cortical myelin could be useful for elucidating its function and how it is modulated during learning and disease.